Design of novel "imprinting synchronized with crosslinking" surface imprinted technique and its application for selectively removing phenols from aqueous solution. (March 2019) - An, Fu-Qiang; Li, Hu-Fei; Guo, Xu-Dong; Hu, Tuo-Ping; Gao, Bao-Jiao; Gao, Jian-Feng
Graphical abstract: The exhausted surface molecularly imprinted polymers (SMIP) could be effectively regenerated by 1 mol L −1 of hydrochloric acid aqueous solution, and the regenerative SMIP could be reused at least 10 times without significant reduction of adsorption capacity and selectivity coefficient. Highlights: A novel efficient surface imprinted technique is well designed. The SMIPs possess strong adsorption ability and excellent recognization selectivity towards template. The recognition selectivity of as-prepared SMIPs is higher than that of other IIPs. The SMIPs have good chemical stability and reusability. Abstract: In this paper, a novel surface molecularly imprinting technique with higher imprinting efficiency is well designed. It really realizes the synchronization of polymer crosslinking and template imprinting. Then the surface molecularly imprinted polymers (SMIPs) are synthesized using 2-nitrophenol (2-NP), 3-nitrophenol (3-NP), 4-nitrophenol (4-NP), and 4-methylphenol (4-MP) as template, respectively. The physicochemical characteristics of SMIPs are characterized by Fourier transform infrared spectroscopy (FTIR) and elemental analysis. The adsorption performances and recognization selectivity of SMIPs towards template are systematically investigated by batch method. The experimental results show that the SMIPs possess strong adsorption ability and excellent selectivity towards template. The selectivity coefficients of 2-NP, 3-NP, 4-NP and 4-MP relative to 4-chlorophenol (4-CP) are 132.2, 124.5, 157.3 and 37.8, respectively. The adsorption process could be well described by the Lagergren-first-order model and Langmuir-monolayer adsorption model. SMIPs have good chemical stability and reusability. The consecutive adsorption-desorption experiments show that the exhausted SMIPs could be effectively regenerated, and the regenerative SMIPs could be reused without significant reduction of adsorption capacity and selectivity coefficient.